2021
DOI: 10.3390/ma14206204
|View full text |Cite
|
Sign up to set email alerts
|

Critical State Theory for the Magnetic Coupling between Soft Ferromagnetic Materials and Type-II Superconductors

Abstract: Improving our understanding of the physical coupling between type-II superconductors (SC) and soft ferromagnetic materials (SFM) is the root for progressing to the application of SC-SFM metastructures in scenarios such as magnetic cloaking, magnetic shielding, and power transmission systems. However, in the latter, some intriguing and yet unexplained phenomena occurred, such as a noticeable rise in the SC energy losses, and a local but not isotropic deformation of its magnetic flux density. These phenomena, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 77 publications
(156 reference statements)
0
9
0
Order By: Relevance
“…Based on our recent findings on the actual magnetostatic coupling between type-II SC wires and SFM materials 37 , in this section we explain not only the physical reasons behind the reported increment on the AC losses above mentioned, but also provide a solution pathway for achieving the maximum reduction of energy losses feasible in multifilamentary rounded MgB wires. For doing so, in Fig.…”
Section: Optimal Metastructure For Maximal Reduction Of Ac Lossesmentioning
confidence: 87%
See 4 more Smart Citations
“…Based on our recent findings on the actual magnetostatic coupling between type-II SC wires and SFM materials 37 , in this section we explain not only the physical reasons behind the reported increment on the AC losses above mentioned, but also provide a solution pathway for achieving the maximum reduction of energy losses feasible in multifilamentary rounded MgB wires. For doing so, in Fig.…”
Section: Optimal Metastructure For Maximal Reduction Of Ac Lossesmentioning
confidence: 87%
“…This is no other than the impact of the magnetostatic coupling between the SC and the SFM sheath shown by Fareed and Ruiz in monocore-wires 37 , whom have demonstrated that no matter the SFM used nor its dimensions, for , the physical coupling between the SC and the SFM leads to a large increment on the electric field outside the SC\SFM metastructure 35 , but not to a further increment in the density of power losses inside the SC. Moreover, this coupling gets dominated by the factor, where , being the SFM-sheath outer radius and its inner radius (outer radius of the Nb(Ti)/MgB filament in our case).…”
Section: Optimal Metastructure For Maximal Reduction Of Ac Lossesmentioning
confidence: 93%
See 3 more Smart Citations